FORMULASI FOODBARS BERBAHAN DASAR TEPUNG KULIT PISANG KEPOK DAN TEPUNG KEDELAI - Chairunnisa Oktofyani Fanzurna; Moh. Taufik (JURNAL BIOINDUSTRI (JOURNAL OF BIOINDUSTRY), 2020)
This study aims to formulate and produce foodbars made from banana peel and soy flour. The use of banana skin aims to utilize food waste that has high enough fiber. The use of soy flour that has high protein. The ratio of the use of kepok banana peel flour and soy flour at formulation F1, F2, F3, F4 and F5 are 50:50, 40:60, 30:70, 20:80 and 10:90 respectively. Banana kepok leather flour produced has a moisture content 5.73%, ash content 11.86%, protein content 6.70%, fat content 16.44% and carbohydrate 59.27%, while soy flour produced has the moisture content 4.80%, ash content 3.88%, protein content 41.64%, fat content 28.44% and carbohydrate 21.24%. Based on the results of the hedonic, F5 was chosen as the selected formula of foodbar. The results of physicochemical characteristic of selected formula with the parameter of moisture content, ash content, protein content, fat content, carbohydrate content, dietary fiber content and texture test levels were 6.70%, 2.71%, 18.79%, 27.20%, 44.60% and 14.76 respectivily